Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - Chapter 11 Review Problem Set - Page 520: 50



Work Step by Step

We first use the FOIL method to simplify the expression. Then, knowing that $i=\sqrt{-1}$, we can substitute $-1$ for $i^{2}$ to obtain: $(-1+i)(-2+6i)$ =$-1(-2+6i)+i(-2+6i)$ =$2-6i-2i+6i^{2}$ =$2-8i+6i^{2}$ =$2-8i+6(-1)$ =$2-6-8i$ =$-4-8i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.